AB1115-HPR Dose Reduction of Biological Therapies in Rheumatoid Arthritis - The Patient's Perspective. (15th July 2016) - Wallis, D.; Holroyd, C.; Sonpal, K.; Zarroug, J.; Adams, J.; Edwards, C.J.
Abstract : Background: Although it is not possible to stop biological therapies for RA patients with established disease, it appears that dose reduction can be successful for some patients in remission or low disease activity. Dose reduction may reduce the risk of adverse events and produce economic benefits that allow greater numbers of patients to receive therapy. Negative consequences might include flares of disease, joint damage and immunogenicity. A vital component of developing dose reduction strategies is to include the patient perspectives. However, these have not been formally reported. Engagement of patients in shared decision-making about their management is vital to improving outcomes and a stated aim of many treatment guidelines. Objectives: To develop a questionnaire, informed by patients and experts, that explores the views of patients with RA about biological therapies and dose reduction. Methods: As a first step in developing a questionnaire we held a patient public involvement (PPI) qualitative focus group (9 patients, 8 female, mean age 49y, mean disease duration 17y) with RA. Eight were on a biological therapy with 2 on a reduced dose. Discussion was facilitated using an interview schedule by two PPI experts and a consultant rheumatologist and recorded. Participants (1) discussed biological therapy in general, (2) listed the top 10 concerns about biological therapy and (3) explored attitudes towards dose reduction. Statements describing the perceived benefits and concerns about dose reduction were separated into two lists and world clouds were generated for each list of statements. Respondent validation of the main themes identified and confirmed the findings. Results: Common themes arising during discussion about biologics in general were: delays in accessing treatment, adverse effects, impact of disease on health, need for education about biologics, inefficacy of previous treatments, impact of disease on family and work and patient autonomy. When exploring attitudes towards dose reduction, the most common concerns were loss of disease control, delay in access to the previous dose and potential loss of efficacy of a previously successful treatment. Perceived benefits were a lower risk of adverse effects and reduced frequency of injection. The positive and negative aspects of dose reduction as cited by patients are shown in word clouds where the size of the word is proportional to the frequency of the word in the patients' statements (Fig 1 ). This work has led to the development of a questionnaire that will be given to a large population of patients receiving biological therapies to assess their views. Conclusions: Patients were prepared to consider dose reduction but need reassurance about rapid access to higher doses should their disease flare. The data provide insight into patients' beliefs and attitudes towards biological therapies and dose reduction and have been used to generate a questionnaire to be distributed to a larger group of patients. The development of a questionnaire that is informed by patient experience and involvement, to explore the views of a wider population of patients, will be an important next step and will assist in the development of patient focussed strategies for dose reduction. Disclosure of Interest: D. Wallis: None declared, C. Holroyd Speakers bureau: BMS, Abbvie, Chugai, Janssen, K. Sonpal: None declared, J. Zarroug: None declared, J. Adams: None declared, C. Edwards Speakers bureau: CE has attended advisory boards, provided consultancy or been part of a speakers bureau for Abbvie, Pfizer, Lilly, Celltrion, Mundipharma, Samsung, Anthera, UCB, Celgene, Roche, BMS, Janssen.